Perpendicular Magnetic Tunnel Junctions Having CoFeB/CoPt Alloy Layers - Choi, Gyung-Min; Min, Byoung-Chul; Shin, Kyung-Ho (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2012)
We have fabricated perpendicular magnetic tunnel junctions consisting of hcp Ru underlayer/hcp CoPt alloy/CoFeB/MgO/CoFeB/CoPt alloy (or Co)/Pt capping layer. By inserting the CoPt alloy (or Co) between the CoFeB and Pt capping layers, it is possible to increase a perpendicular magnetic anisotropy of the top electrode. Using a top electrode of Co40Fe40B20(0.4 nm)nm/Co72Pt28(1.6 nm)/Pt, we have obtained an effective magnetic anisotropy of 3.3 x 10(6) crg/cm(3) and a tunnel magnetoresistance (TMR) of 9.4%. The analysis of the crystal structure reveals that the low TMR is a consequence of the fcc (111) texture of CoFeB layers.